'No longer believing in belonging': A longitudinal study of Finnish Generation Y from confirmation experience to Church-leaving. (June 2015) - Niemelä, Kati
The prevailing attitude to the national churches in the Nordic countries has often been described as 'believing in belonging'. Based on a longitudinal survey data, this article argues that this notion no longer applies to the younger generation, often referred to as Generation Y. Instead, they are challenging traditional reasons for belonging to national churches. The number of church-leavers has been unusually high in Finland since the beginning of the 21st century, the vast majority of them young adults. These same young adults were confirmed in the church only a few years earlier. This study aims to understand why such a high number of young people leave the Evangelical Lutheran Church soon after confirmation. The study shows that for Generation Y, the Church-leaving process is linked to personal beliefs and values. They leave the Church because they do not find it to be in line with their own beliefs. Tradition and culture alone are not enough to keep them as members.